The effect of 3-months trigona honey supplementation and associated factors on the progression of mild post-ischaemic stroke cognitive impairment at Hospital Universiti Sains Malaysia: a unicentral randomised controlled trial - Abdalla, Renad Sadig Muhammed (2023)
Background: Affecting up to 80% of ischaemic stroke patients, post-stroke cognitive impairment (PSCI) is a complication that predicts poor quality of life and restricted activity and has also been associated with decreased independence and substantial caretaker and economic burden. Despite the wider attention directed towards stroke sequelae, PSCI remains a major post-stroke complication with limited therapeutic options. Based on current understanding of the pathogenesis of PSCI, Trigona honey makes an attractive therapeutic option, as it can act on numerous neuropathological substrates implicated in PSCI’s pathogenesis via the action of multiple polyphenols. Objectives: To investigate possible benefits of Trigona honey supplements in halting progression of mild PSCI in acute ischaemic stroke patients admitted to Hospital Universiti Sains Malaysia (HUSM). The study also investigated the effect of demographic and clinical characteristics, stroke severity, and pathophysiological subtype and vascular territory on the progression of PSCI. Methods: The study was conducted at Neurology Ward and Specialist Clinic at HUSM, following a unicentral, randomised, concurrent active treatment controlled, open-label superiority trial with two parallel groups model. The interventional group included participants who were administered supplemental honey in addition to standard care regiments, while those in the control group solely continued the standard therapeutic protocol. 48 acute ischaemic stroke patients between the ages of 20 and 70 years old and suffering from mild PSCI were recruited and equally randomised between the two groups. Patients with impeded ability to answer the neuropsychological assessments or are suffering from compromised cognitive functions prior to the stroke were excluded. Two honey sachets were administered for daily oral consumption for the duration of 12 weeks, with a total daily dose of 20 g. Demographic data and clinical characteristics questionnaire, MoCA, and NIHSS were used for data collection. Data collected was analysed using SPSS software. Results and Discussion: Difference in mean gain in MoCA score between the two groups after three months was statistically significant (p = 0.007), with the interventional group having greater mean gain by 3 points. No statistically significant relationship between demographic and clinical characteristics, stroke parameters, and 3-months progression of PSCI was detected, possibly due to small sample size. The only exception was an improved cognitive function in current smokers in the interventional group (p = 0.01, β = 0.514), possibly due to smoking cessation. Conclusion: Trigona honey supplements were effective in halting progression of PSCI, and smoking can affect 3-months progression of PSCI. However, stroke severity, TOAST and OCSP classifications had no effect on 3-months progression of PSCI. While conclusions from this study can be helpful in guiding hypotheses about the employment of Trigona honey in the therapy for PSCI, as well as the different factors and predictors influencing the trajectory of PSCI, they must first be confirmed in a larger population and in homogenous groups.